AKUNTABILITAS PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA DI DESA TELANGKAH KECAMATAN KATINGAN HILIR KABUPATEN KATINGAN - Fitriani; Ahia Novie (Jurusan Ilmu Pemerintahan, 2018)
This research focuses attention on applying the principle of accountability in the management of Village Revenue and Expenditure Budget (APBDesa) in order to describe the accountability of the management of this APBDesa starting from the stages of planning, implementation, administration, reporting and accountability. This research was conducted in the Telangkah Village Katingan Hilir Sub District Katingan Regency. The results of the research show that: in the planning, implementation and administration phase in accordance with the applicable procedures proved by the existing physical and non-physical development and financial management has been done transparently and accountably. Reporting and Accountability have been well implemented by the village government as all the plans outlined in the 2017 APBDesa have been realized and reported to the district government with copies to the Inspectorate. So it can be accounted for in vertical and horizontal accountability. Factors affecting the accountability of the management of the Village Budget and Expenditures include supporting factors: community participation and village administration. inhibiting factors: lack of human resources, poor facilities and the presence of village income. Suggestions for village government in the implementation of village financial management should maintain accountability principles. Keywords: Accountability, Village Financial Management, APBDesa